2008
DOI: 10.1073/pnas.0710263105
|View full text |Cite
|
Sign up to set email alerts
|

Loss of microRNA cluster miR-29a/b-1 in sporadic Alzheimer's disease correlates with increased BACE1/β-secretase expression

Abstract: Although the role of APP and PSEN genes in genetic Alzheimer's disease (AD) cases is well established, fairly little is known about the molecular mechanisms affecting A␤ generation in sporadic AD. Deficiency in A␤ clearance is certainly a possibility, but increased expression of proteins like APP or BACE1/␤-secretase may also be associated with the disease. We therefore investigated changes in microRNA (miRNA) expression profiles of sporadic AD patients and found that several miRNAs potentially involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
967
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,053 publications
(1,010 citation statements)
references
References 52 publications
39
967
1
3
Order By: Relevance
“…Previous reports demonstrate that miR-101 is downregulated in the temporal and parietal cortices of patients with AD. 32 Notably, miR-101 is shown to downregulate APP and fibrillar Ab in hippocampal neurons by directly targeting APP 33 or RanBP9, which encodes for the RanBP9 protein to enhance the proteolytic processing of APP and Ab generation both in vivo and in vitro. 34 In the present study, we demonstrate that miR-101b directly targets the 3 0 UTR of AMPK to post-transcriptionally regulate its protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrate that miR-101 is downregulated in the temporal and parietal cortices of patients with AD. 32 Notably, miR-101 is shown to downregulate APP and fibrillar Ab in hippocampal neurons by directly targeting APP 33 or RanBP9, which encodes for the RanBP9 protein to enhance the proteolytic processing of APP and Ab generation both in vivo and in vitro. 34 In the present study, we demonstrate that miR-101b directly targets the 3 0 UTR of AMPK to post-transcriptionally regulate its protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-29a/b-1 cluster is decreased in sporadic AD patients, and it has been demonstrated that miR-29a/b-1 also regulates BACE1 expression (43). The study by Wang et al (46) demonstrated that miR-107 expression is decreased significantly in the cortex of AD patients, even at extremely early pathological alterations.…”
Section: Alzheimer's Diseasementioning
confidence: 98%
“…miR-298 and miR-328 play important roles by repressing the expression of β-amyloid precursor protein-converting enzyme 1 (BACE1), which causes amyloid-β (Aβ) overproduction in cultured neuronal cells (43). The miR-29a/b-1 cluster is decreased in sporadic AD patients, and it has been demonstrated that miR-29a/b-1 also regulates BACE1 expression (43).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…As miR-29a, miR-29b-1, and miR-9 were found to regulate BACE1 expression in reporter gene assays performed in transiently transfected HeLa cells, the miR-29a/b-1 cluster was significantly decreased in AD patients displaying abnormally high BACE1 protein levels (Hebert et al, 2008). Providing support for a causal relationship between miR-29a/b-1 expression and AD, these findings led the authors to propose that loss of specific miRNAs can contribute to increased BACE1 and Aβ levels in sporadic AD, as illustrated in Figure 1C.…”
Section: Micrornas and Alzheimer's Diseasementioning
confidence: 95%
“…Although a deficiency in Aβ clearance is certainly a possibility, an increased expression of the Aβ-producing enzyme BACE1 may also be an important contributor to the net accumulation of Aβ peptides and AD progression (Hebert et al, 2008). This assertion is supported by the observed dosage effect of BACE1 in inducing AD (Rovelet-Lecrux et al, 2006), suggesting that any alterations in BACE1 expression levels might contribute to the disease.…”
Section: Micrornas and Alzheimer's Diseasementioning
confidence: 99%